Comparison of diabetic and idiopathic sensory polyneuropathies with respect to nerve fibre affection and risk factors. Issue 1 (14th March 2022) - Itani, Mustapha; Gylfadottir, Sif; Krøigård, Thomas; Gaist, Laura; Holbech, Jakob Vormstrup; Kristensen, Alexander Gramm; Karlsson, Pall; Möller, Sören; Tankisi, Hatice; Gaist, David; Jensen, Troels S; Finnerup, Nanna Brix; et al.
Abstract : Background and purpose: Chronic distal sensory or sensorimotor polyneuropathy is the most common pattern of polyneuropathy. The cause of this pattern is most often diabetes or unknown. This cross-sectional study is one of the first studies to compare the demographics, cardiovascular risk factors and clinical characteristics of diabetic polyneuropathy (DPN) with idiopathic polyneuropathy (IPN). Methods: Patients with DPN were included from a sample of 389 patients with type 2 diabetes mellitus (T2DM) enrolled from a national cohort of patients with recently diagnosed T2DM (Danish Centre for Strategic Research in Type 2 Diabetes cohort). Patients with IPN were included from a regional cohort of patients with symptoms of polyneuropathy referred for workup at a combined secondary and tertiary neurological centre (database cohort). Results: A total of 214 patients with DPN were compared with a total of 88 patients with IPN. Patients with DPN were older (67.4 vs 59 years) and had a longer duration of neuropathy symptoms. Patients with DPN had greater body mass index (32 vs 27.4 kg/m 2 ) and waist circumference (110 cm vs 97 cm); higher frequency of hypertension diagnosis (72.9% vs 30.7%); lower total cholesterol, low-density lipoprotein cholesterol and high-density lipoprotein cholesterol levels; and a higher prevalence of use of statins (81.8% vs 19.3%). DPN was associated with a slightly higher autonomic score and total score on the Neuropathy Symptom Score; lower frequency of hyperalgesia, allodynia and decreased vibration on quantitative sensory testing; lower intraepidermal nerve fibre density count and higher frequency of small-fibre neuropathy. Conclusion: DPN and IPN showed clear differences in neuropathy characteristics, indicating that these two entities are to be regarded as aetiologically and pathogenetically distinct.